Characterization of ZnO thin films grown on different p-Si substrate elaborated by solgel spin-coating method. (October 2015) - Chebil, W.; Fouzri, A.; Fargi, A.; Azeza, B.; Zaaboub, Z.; Sallet, V.
Graphical abstract: Highlights: High quality ZnO thin films grown on different p-Si substrates were successful obtained by sol–gel process. PL measurement revealed that ZnO thin film grown on porous Si has the better optical quality. I – V characteristics for all heterojunctions exhibit successful diode formation. The diode ZnO/PSi shows a better photovoltaic effect under illumination with a maximum V oc of 0.2 V. Abstract: In this study, ZnO thin films are deposited by sol–gel technique on p-type crystalline silicon (Si) with [100] orientation, etched silicon and porous silicon. The structural analyses showed that the obtained thin films were polycrystalline with a hexagonal wurtzite structure and preferentially oriented along the c -axis direction. Morphological study revealed the presence of rounded and facetted grains irregularly distributed on the surface of all samples. PL spectra at room temperature revealed that ZnO thin film grown on porous Si has a strong UV emission with low defects in the visible region comparing with ZnO grown on plat Si and etched Si surface. The heterojunction parameters were evaluated from the ( I – V ) under dark and illumination at room temperature. The ideality factor, barrier height and series resistance of heterojunction grown on different p-Si substrates are determined by using different methods. Best electrical properties are obtained for ZnO layer deposited on porous silicon.